TENCON 2018 - 2018 IEEE Region 10 Conference 2018
DOI: 10.1109/tencon.2018.8650491
|View full text |Cite
|
Sign up to set email alerts
|

Deep Neural Networks with Weighted Averaged Overnight Airflow Features for Sleep Apnea-Hypopnea Severity Classification

Abstract: Dramatic raising of Deep Learning (DL) approach and its capability in biomedical applications lead us to explore the advantages of using DL for sleep Apnea-Hypopnea severity classification. To reduce the complexity of clinical diagnosis using Polysomnography (PSG), which is multiple sensing platform, we incorporates our proposed DL scheme into one single Airflow (AF) sensing signal (subset of PSG). Seventeen features have been extracted from AF and then fed into Deep Neural Networks to classify in two studies.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 22 publications
1
29
0
Order By: Relevance
“…A recent comprehensive survey showed that the vast majority of deep learning methods for sleep breathing disorders have been devoted to signals [ 46 ]. Few studies considered single channel respiration inputs for deep learning apnea detection models [ 58 , 59 , 60 , 61 ]. Convolutional neural networks were used in [ 58 , 59 , 61 ] while [ 60 ] used human-engineered features as an input to a deeply stacked feed-forward neural network but none of them have evaluated recurrent neural networks.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A recent comprehensive survey showed that the vast majority of deep learning methods for sleep breathing disorders have been devoted to signals [ 46 ]. Few studies considered single channel respiration inputs for deep learning apnea detection models [ 58 , 59 , 60 , 61 ]. Convolutional neural networks were used in [ 58 , 59 , 61 ] while [ 60 ] used human-engineered features as an input to a deeply stacked feed-forward neural network but none of them have evaluated recurrent neural networks.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies considered single channel respiration inputs for deep learning apnea detection models [ 58 , 59 , 60 , 61 ]. Convolutional neural networks were used in [ 58 , 59 , 61 ] while [ 60 ] used human-engineered features as an input to a deeply stacked feed-forward neural network but none of them have evaluated recurrent neural networks. Although CNNs are widely used in deep learning methods, they require very high computational power as opposed to RNNs and are also designed to work with images unlike RNNs that are fundamentally used for signals with temporal dependencies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PSG can only be used in specialized clinics or hospitals under constant medical supervision to collect physiological signals from patients with sleep disorders, and then use professional sleep experts to diagnose patients who are sleep disorders based on physiological signals detected by PSG [7] This means that patients must go to specialized medical institutions, which will inevitably increase the burden on patients. Moreover, PSG requires the integration of many sensors on the human body, which is considered invasive, so PSG screening can interfere with sleep [8]. In addition, PSG is costly and time consuming, plus the need for professional sleep experts.…”
Section: Introductionmentioning
confidence: 99%